0=x2-3x-40

Rewrite the equation as x2-3x-40=0.

x2-3x-40=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -40 and whose sum is -3.

-8,5

Write the factored form using these integers.

(x-8)(x+5)=0

(x-8)(x+5)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-8=0

x+5=0

Set the first factor equal to 0.

x-8=0

Add 8 to both sides of the equation.

x=8

x=8

Set the next factor equal to 0.

x+5=0

Subtract 5 from both sides of the equation.

x=-5

x=-5

The final solution is all the values that make (x-8)(x+5)=0 true.

x=8,-5

Solve using the Square Root Property 0=x^2-3x-40